Influence of habitual dietary fibre intake on the responsiveness of the gut microbiota to a prebiotic: protocol for a randomised, double-blind, placebo-controlled, cross-over, single-centre study. Issue 9 (2nd September 2016) - Healey, Genelle; Brough, Louise; Butts, Chrissie; Murphy, Rinki; Whelan, Kevin; Coad, Jane
Abstract : Introduction: The commensal gut microbiota have been shown to have an impact on human health as aberrant gut microbiota have been linked to disease. Dietary constituents are influential in shaping the gut microbiota. Diet-specific therapeutic strategies may therefore play a role in optimising human health via beneficial manipulation of the gut microbiota. Research has suggested that an individual's baseline gut microbiota composition may influence how the gut microbiota respond to a dietary intervention and individuals with differing habitual dietary intakes appear to have distinct baseline gut microbiota compositions. The responsiveness of the gut microbiota may therefore be influenced by habitual dietary intakes. This study aims to investigate what influence differing habitual dietary fibre intakes have on the responsiveness of the gut microbiota to a prebiotic intervention. Methods and analysis: In this randomised, double-blind, placebo-controlled, cross-over, single-centre study, 20 low dietary fibre (dietary fibre intake <18 g/day for females and <22 g/day for males) and 20 high dietary fibre (dietary fibre intake ≥25 g/day for females and ≥30 g/day for males) consumers will be recruited. Participants will be randomised to a placebo (Glucidex 29 Premium) or a prebiotic (Synergy 1) intervention for 3 weeks with a 3-week washout followed by 3 weeks of the alternative intervention. Outcome measures of gut microbiota composition (using 16S rRNA gene sequencing) and functional capacity (faecal short chain fatty acid concentrations and Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt)) as well as appetite (visual analogue scale appetite questionnaire) will be assessed at the beginning and end of each intervention phase. Ethics and dissemination: The Massey University Human Ethics Committee approved this study (Massey University HEC: Southern A application—15/34). Results will be disseminated through peer-review journal publications, conference presentations and a summary of findings will be distributed to participants. Trial registration number: ACTRN12615000922572 ; Pre-results.